Hydration and sweating responses to hot-weather football competition - Kurdak, S. S.; Shirreffs, S. M.; Maughan, R. J.; Ozgünen, K. T.; Zeren, C.; Korkmaz, S.; Yazici, Z.; Ersöz, G.; Binnet, M. S.; Dvorak, J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
During a football match played in warm (34.3 ± 0.6 °C), humid (64 ± 2% rh) conditions, 22 male players had their pre-match hydration status, body mass change, sweat loss and drinking behavior assessed. Pre-match urine specific gravity (1.012 ± 0.006) suggested that all but three players commenced the match euhydrated. Players lost 3.1 ± 0.6 L of sweat and 45 ± 9 mmol of sodium during the 90-min match and replaced 55 ± 19% of their sweat losses and hence by the end of the game were 2.2 ± 0.9% lighter. The water volume consumed during the game was highly variable (1653 ± 487 mL; 741-2387 mL) but there was a stronger relationship between the estimated pre-game hydration status and water volume consumed, than between sweat rate and water volume consumed. In a second match, with the same players 2 weeks later in 34.4 ± 0.6 °C, 65 ± 3% rh, 11 players had a sports drink available to them before and during the match in addition to water. Total drink volume consumed during the match was the same, but approximately half the volume was consumed as sports drink. The results indicate that substantial sweat water and electrolyte losses can occur during match play in hot conditions and a substantial water and sodium deficit can occur in many players even when water or sports drink is freely available.